The result of treadmill test in asymptomatic type 2 diabetes mellitus - Joshi, Anil Shrinivasrao; Lahane, Chandrakant Gunaji; Kashid, Akshay Arvind (International Journal of Scientific Reports, 2017)
Background: To study the prevalence of silent myocardial ischaemia in asymptomatic patients with type 2 DM. Methods: The present study was conducted in the Govt. Medical College and Hospital Aurangabad. During December 2012 to November 2014 with 50 patients. It was two year cross sectional study with the patients of asymptomatic type 2 diabetes mellitus without clinical and electrocardiographic evidence of coronary artery disease. Results: 12 (24%) out of 50 subjects had positive TMT. It correlated with years of duration of diabetes (9 positive TMT cases with duration of diabetes more than 10 years). 5 (25%) out of 20 had serum cholesterol levels >240, Number of positive TMT were higher in patients with LDL >160 [5 (25%) out of 20]. Conclusions: Diabetic patients are at very high risk for cardiovascular morbidity and mortality. Early detection of IHD is very important so that pharmacological therapy, which may improve outcome, can be established. Tread mill exercise TMT being a non-invasive test with high safety, has an important role in early detection of IHD. It is recommended that TMT should be a part of routine management in asymptomatic patients with type II DM.